PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKn) DENGAN MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE GROUP INVESTIGATION (GI) - Apriani, Ade (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research was a class action that aims to improve the learning outcomes of civic education using the model Group Investigation (GI)in class IV SDN 02 Indarung. The approach used is a qualitative and quantitative approach. The data source is the process and results of the implementation of learning civic education by using model  Group Investigation (GI). The result showed improvement of student learning  outcomes. The results showed improvement of various aspects of the learning plan in the first cycle was 81% in the second cycle was 92%, observed aspects of teachers in the first cycle was 83.5% in the second cycle was 96%, observed aspects of students' first cycle was 83 , 5% in the second cycle was 96%, the first cycle of learning outcomes is increased in the second cycle 70.8 to 85.4. Thus, models of Group Investigation (GI) can improve the learning outcomes of civic education. Kata Kunci : hasil belajar PKn, model Cooperative Learning tipe Group Investigation (GI), siswa SD